Analysis of the Content of High School Biology Textbooks in Jordan in Terms of Next Generation Science Standards (NGSS) - Abduallah Salem Alzoubi (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The aim of this study is to analyze the content of biology textbooks for secondary grades in Jordan and to investigate the proportions of the next generation science standards (NGSS). In order to achieve this, the study applied an analytical descriptive approach in analyzing the content of biology books for secondary grades in the academic year (2017-2018). The researcher prepared a questionnaire which included the criteria of science for future generations as categories of analysis, and verified its validity and stability. The results showed that the scope of cognitive content in the books of biology of secondary stage is not sufficiently consistent with science standards for future generations, There are gaps in the coverage of some areas, such as the areas of matter and energy, size, proportion and quantity, the construction of explanations in science, the design of solutions in engineering, and the use of mathematical thinking.